(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article examines the sources of financing the social services market and identifies ways to improve their efficiency. The study analyzes the role of state budget funds, extra-budgetary resources, private sector participation, public-private partnership mechanisms, grants, and social investment instruments in ensuring the sustainable development of social services. Particular attention is paid to the efficient allocation of financial resources, transparency of funding mechanisms, targeted support for vulnerable groups, and the improvement of service quality. The article substantiates that diversifying financing sources, strengthening institutional mechanisms, introducing performance-based funding, and expanding digital monitoring systems can significantly increase the efficiency of the social services market.